Targeting of vulnerabilities of drug-tolerant persisters identified through functional genetics delays tumor relapse - Chen, Mengnuo; Mainardi, Sara; Lieftink, Cor; Velds, Arno; de Rink, Iris; Yang, Chen; Kuiken, Hendrik J.; Morris, Ben; Edwards, Finn; Jochems, Fleur; van Tellingen, Olaf; Boeije, Manon; et al. (Cell reports. Medicine, 2024)
Drug-tolerant persisters (DTPs) are a rare subpopulation of cells within a tumor that can survive therapy through nongenetic adaptive mechanisms to develop relapse and repopulate the tumor following drug withdrawal. Using a cancer cell line with an engineered suicide switch to kill proliferating cells, we perform both genetic screens and compound screens to identify the inhibition of bromodomain and extraterminal domain (BET) proteins as a selective vulnerability of DTPs. BET inhibitors are especially detrimental to DTPs that have reentered the cell cycle (DTEPs) in a broad spectrum of cancer types. Mechanistically, BET inhibition induces lethal levels of ROS through the suppression of redox-regulating genes highly expressed in DTPs, including GPX2, ALDH3A1, and MGST1. In vivo BET inhibitor treatment delays tumor relapse in both melanoma and lung cancer. Our study suggests that combining standard of care therapy with BET inhibitors to eliminate residual persister cells is a promising therapeutic strategy. [Display omitted] •Unbiased genetic screen and compound screen identify BRD2 as a vulnerability of DTPs•BET inhibitors suppress outgrowth of DTPs in a broad spectrum of cancer types•BET inhibitors suppress DTEPs through transcriptional repression of GPX2/ALDH3A1/MGST1•BET inhibitors delay tumor relapse Chen et al. uses high-throughput screening approaches to identify BRD2 inhibition as a vulnerability of drug-tolerant persisters (DTPs). They further demonstrate that BET inhibitors suppress the emergence of DTPs in multiple cancer cell lines in vitro and can forestall drug resistance through the eradication of DTPs in vivo.